2018
DOI: 10.1371/journal.pone.0192208
|View full text |Cite
|
Sign up to set email alerts
|

The effect of S100A6 on nuclear translocation of CacyBP/SIP in colon cancer cells

Abstract: BackgroundCalcyclin Binding Protein/(Siah-1 interacting protein) (CacyBP/SIP) acts as an oncogene in colorectal cancer. The nuclear accumulation of CacyBP/SIP has been linked to the proliferation of cancer cells. It has been reported that intracellular Ca2+ induces the nuclear translocation of CacyBP/SIP. However, the molecular mechanism of CacyBP/SIP nuclear translocation has yet to be elucidated. The purpose of this study was to test whether the Ca2+-dependent binding partner S100 protein is involved in Cacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
(27 reference statements)
2
6
0
Order By: Relevance
“…As Cacybp is an E3 ubiquitin ligase, we hypothesized that the 46 downregulated genes may include ubiquitinated substrates of Cacybp. The current focus of research is mainly Cacybp nuclear transfer (11,13,21,22) and phosphorylation activities (23)(24)(25)(26), which is consistent with our results. Using Cytoscape software we identified biological processes and molecular functions that may be affected by Cacybp.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…As Cacybp is an E3 ubiquitin ligase, we hypothesized that the 46 downregulated genes may include ubiquitinated substrates of Cacybp. The current focus of research is mainly Cacybp nuclear transfer (11,13,21,22) and phosphorylation activities (23)(24)(25)(26), which is consistent with our results. Using Cytoscape software we identified biological processes and molecular functions that may be affected by Cacybp.…”
Section: Discussionsupporting
confidence: 91%
“…We identified genes closely related to Cacybp expression through bioinformatics software analysis, but determining which of these differential genes are targets of Cacybp and which are ubiquitinated substrates requires further study. The current focus of research is mainly Cacybp nuclear transfer (11,13,21,22) and phosphorylation activities (23)(24)(25)(26), which is consistent with our results. In addition, we also found that Cacybp is involved in cell secretion and examined Cacybp expression in glioma patients and its relationship with prognosis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations